(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
This paper has emphasized that agriculture was the mother of the overall economy of the pre-colonial West African sub-African sub-region with the Hausaland as a case study. It shows the strong connection and interconnection with other aspect of the economy particularly in the nineteenth century. Other aspect of the economy such as trade and craft defended strongly on agriculture. In other words, agriculture feeds both trade and craft. Further, the paper has threw into the dustbin all the comments made by some of the Eurocentric that West Africa pre-colonial economy was primitive, stagnant, subsistence and it lack real market status before their arrival (colonialism)